Phytoplankton and Periphyton Primary Production in Clear and Turbid Shallow Lakes: Influence of the Light Environment on the Interactions between these Communities - Sánchez, María Laura (2017)
The ecological relevance of shallow lakes has been largely documented. The Pampean plain (Argentina) holds one of the main wetlands of South America, constituted by thousands of shallow lakes which provide valuable ecosystem services, and can be found in any of three regimes: clear-vegetated, inorganic-turbid or phytoplankton-turbid. Since these lakes play an important role in the global carbon balance, metabolism studies encompassing phytoplankton and periphyton under different regimes become relevant. Here, we analyzed the primary production (PP) of phytoplankton and periphyton in three Pampean shallow lakes representing the main types mentioned. The relative contribution of each algal community to the joint PP was different in each lake and related to their regime. The periphyton contribution was higher in the clear-vegetated lake than in the turbid lakes. The phytoplankton-turbid lake exhibited the highest PP for both communities. The inorganic-turbid lake presented the highest light limitation; nonetheless, the efficiency of periphyton in this lake showed an increasing trend with depth, suggesting light acclimation. Although phytoplankton dominated the PP in the three lakes, periphyton contribution was also important, particularly in the clear-vegetated lake. Our results emphasize that the PP of attached communities should be considered to estimate the PP of the whole lake.